An introduction to anthropology - Beals, Ralph Leon; Hoijer, Harry;Beals, Alan R. (New York : Macmillan Publishing Company, 1977)
This book is primarily a book about culture. It provides information about the ways in which the concept of culture has been defined; it explores the expressions of culture found among different peoples.
1. The nature and scope of anthropology -- 2. The nature of culture -- 3. Strategies and methods in the study of culture -- 4. Human biological variation -- 5. The evolution of humanity -- 6. Culture in the past -- 7. Hunter-gatherers -- 8. Food producers -- 9. Food production and urban life -- 10. Economic anthropology -- 11. Marriage -- 12. Kinship and kinship groupings -- 13. Social organization.
Includes bibliographical references and index.
Keywords: ANTHROPOLOGY